Desert puffballs from Ladakh trans-Himalaya (J&K), India -the genus Bovista and Calvatia - Y.P. SHARMA*, KONCHOK DORJEY, SANJEEV KUMAR and (Indian Phytopathology, 2016)
Present study emphasizes on the documentation of some hitherto interesting unrecorded puffballs from cold arid Ladakh region of Indian Trans-Himalaya, from where very few reports exist on the macrofungi. During the year 2011-13, five taxa of puffballs namely Bovista minor, B. plumbea, B. plumbeavar. dens-caulis, B. pusilla and Calvatia bovista were recorded. Out of these, B. minor and C. bovista constitute new records for India whereas B. plumbea and B. pusilla were recorded for the first time from Ladakh region of Jammu and Kashmir State. In addition, B. plumbea var. dens-caulis is being proposed as a new variety. Detailed description of habitat, macro- and microscopic characteristics and their edibility have been provided with taxonomic key, photographs and illustrations.